2014
DOI: 10.1105/tpc.114.127647
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DELLA and Two HD-ZIP Transcription Factors Regulate GA Signaling in the Epidermis through the L1 Box cis-Element  

Abstract: Gibberellins (GAs) are plant hormones that affect plant growth and regulate gene expression differentially across tissues. To study the molecular mechanisms underlying GA signaling in Arabidopsis thaliana, we focused on a GDSL lipase gene (LIP1) induced by GA and repressed by DELLA proteins. LIP1 contains an L1 box promoter sequence, conserved in the promoters of epidermis-specific genes, that is bound by ATML1, an HD-ZIP transcription factor required for epidermis specification. In this study, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 97 publications
(184 reference statements)
3
77
0
Order By: Relevance
“…The GA signaling repressor DELLA interferes with this process through competitive binding to GhHOX3, thus transducing GA signal to cotton fiber growth (Shan et al ., ). Similar interaction also functions in Arabidopsis in mediating hypocotyl epidermal cell growth (Rombola‐Caldentey et al ., ), suggesting that this is a general mechanism that promotes plant cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GA signaling repressor DELLA interferes with this process through competitive binding to GhHOX3, thus transducing GA signal to cotton fiber growth (Shan et al ., ). Similar interaction also functions in Arabidopsis in mediating hypocotyl epidermal cell growth (Rombola‐Caldentey et al ., ), suggesting that this is a general mechanism that promotes plant cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the GL1type MYBs may also play a role, because all homoeologs of the Arabidopsis MYB-bHLH-WD40 (MBW) complex (Szymanski et al, 2000) are expressed in cotton fibers (Shangguan et al, 2008). During elongation, the phytohormone gibberellin (GA) plays a key role in promoting fiber growth, during which GhHOX3, an homoeodomain leucine zipper (HD-ZIP) IV transcription factor, acts as a core regulator (Rombola-Caldentey et al, 2014;Shan et al, 2014). Because cell elongation involves multiple signaling pathways and cotton fiber cells are unique in their extensive and synchronous elongation, isolation of new regulators will further our understanding of the molecular basis of cotton fiber development and of plant cell growth in general.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dissection of GL2, a member of the HD-Zip IV family in Arabidopsis, has suggested that the START domain is required for stimulating its transcription factor activity via binding of an as yet unidentified ligand, although it is not strictly necessary for the protein's nuclear localization (Schrick et al 2014). Both ATML1 and PDF2 have been shown to interact directly with DELLA proteins, which blocks gibberellin signaling required for seed germination (Rombolá-Caldentey et al 2014), although the DELLA-binding domain remains to be determined. It seems likely that pdf2-1 and pdf2-2 mutant proteins are free from the control by ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, DELLAs sequester two HD-ZIP transcription factors, namely, ATML1 and PDF2, and thereby block GA signaling in the epidermis under low GA conditions. However, upon imbibition, ATML1/PDF2 are released from DEL-LAs and become free to activate EXPA8 and epidermis-specific GDSL lipase gene (LIP1) expression, thereby initiating elongation of epidermal cells to allow seeds to germinate (Rombolá -Caldentey et al, 2014).…”
Section: Biophysical Forces Associated With Seed Germination Are Regumentioning
confidence: 99%